Lessons from an Evaluation of an RPL Project in Further Education and Training in Ireland (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2023)
Tobar was a pilot cohort project in the recognition of prior learning (RPL) that ran in 10 Education and Training Boards (ETBs) in Ireland, in partnership with the Irish Defence Forces (DF). The project, which gets its name from the Irish word for “well” or “spring,”, a reference to people’s life experience as a source of knowledge, enabled soldiers to use their military and other learning to demonstrate learning outcomes required for gaining awards at levels 2 to 5 (EQF, European Qualification Framework). This required a “boundary crossing” between the disorganized amalgam of prior experiential knowledge and the codified knowledge of the qualification. As of December 2020, a total of 91 learners had achieved 386 component minor awards, with 21 of these also achieving major awards. Coming together as a group of Further Education and Training (FET) providers, under the auspices of Education and Training Boards Ireland (ETBI), enabled the providers to share knowledge, mobilize collective intelligence, take account of the systemic nature of RPL issues, and increase confidence in the use of RPL at the local level using a common approach. Based on the conclusions, recommendations are proposed for incremental mainstreaming of RPL, according to three different levels — strategy, structure, and practice. These features of the project provide valuable lessons for the mainstreaming of RPL in VET provision more generally.